Assessment of Work of Breathing in Patients with Acute Exacerbations of Chronic Obstructive Pulmonary Disease. (2nd November 2019) - Barrett, N. A.; Hart, N.; Camporota, L.
Abstract: The assessment of the work of breathing (WOB) of patients with acute exacerbations of chronic obstructive pulmonary disease (COPD) is difficult, particularly when the patient first presents with acute hypercapnia and respiratory acidosis. Acute exacerbations of COPD patients are in significant respiratory distress and noninvasive measurements of WOB are easier for the patient to tolerate. Given the interest in using alternative therapies to noninvasive ventilation, such as high flow nasal oxygen therapy or extracorporeal carbon dioxide removal, understanding the physiological changes are key and this includes assessment of WOB. This narrative review considers the role of three different methods of assessing WOB in patients with acute exacerbations of COPD. Esophageal pressure is a very well validated measure of WOB, however the ability of patients with acute exacerbations of COPD to tolerate esophageal tubes is poor. Noninvasive alternative measurements include parasternal electromyography (EMG) and electrical impedance tomography (EIT). EMG is easily applied and is a well validated measure of neural drive but is more likely to be degraded by the electrical environment in intensive care or high dependency. EIT is less well validated as a tool for WOB in COPD but extremely well tolerated by patients. Each of the different methods assess WOB in a different way and have different advantages and disadvantages. For research into therapies treating acute exacerbations of COPD, combinations of EIT, EMG and esophageal pressure are likely to be better than only one of these.